2023
DOI: 10.1186/s13098-023-00998-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential clinical biomarkers and perspectives in diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a serious cardiovascular complication and the leading cause of death in diabetic patients. Patients typically do not experience any symptoms and have normal systolic and diastolic cardiac functions in the early stages of DCM. Because the majority of cardiac tissue has already been destroyed by the time DCM is detected, research must be conducted on biomarkers for early DCM, early diagnosis of DCM patients, and early symptomatic management to minimize mortality rates among DCM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 147 publications
0
4
0
Order By: Relevance
“…It can also facilitate the progression of HF in diabetic hearts by promoting lipotoxicity and the generation of ROS [40]. ANP and BNP are two major HF markers released into the serum from the hypertrophied cardiac wall stain [41,42]. In addition, LDH, CK-MB, and TPI are important markers for assessing cardiomyocyte injury, as they are released from the damaged cardiomyocytes and are markers of cell membrane disintegration [43].…”
Section: Discussionmentioning
confidence: 99%
“…It can also facilitate the progression of HF in diabetic hearts by promoting lipotoxicity and the generation of ROS [40]. ANP and BNP are two major HF markers released into the serum from the hypertrophied cardiac wall stain [41,42]. In addition, LDH, CK-MB, and TPI are important markers for assessing cardiomyocyte injury, as they are released from the damaged cardiomyocytes and are markers of cell membrane disintegration [43].…”
Section: Discussionmentioning
confidence: 99%
“…The detection of serum markers, such as increased inflammatory mediators (TNFα, isoprostanes, IL-6, and C-reactive protein), elevated fibrotic markers (TGFβ1 and IGFBP7) and decreased antioxidant markers (leptin, adiponectin, and bilirubin), can also provide a basis for the early diagnosis and treatment of DCM [ 12 ]. Recent studies have shown that a number of new novel markers, such as galactin-3 (Gal-3), adiponectin (APN), and irisin, are significantly changed in the clinical course of the various stages of DCM [ 13 ]. Moreover, evidence suggests that exosomes, microRNAs, and long noncoding RNAs have potential applications as biomarkers for the detection of DCM [ 14 , 15 ].…”
Section: Clinical Symptoms and Diagnosis Of Dcmmentioning
confidence: 99%
“…Diabetic cardiomyopathy (DCM) is a common cardiovascular complication in diabetic patients characterized by fibrosis, stiffness, and hypertrophy that induce adverse cardiac structure and performance with consequent diastolic and systolic dysfunction [ 1 ]. In severe conditions, DCM can evolve into heart failure, an alteration of cardiac structure/function, inducing an inadequate cardiac output, and an increased left ventricular filling pressure [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In severe conditions, DCM can evolve into heart failure, an alteration of cardiac structure/function, inducing an inadequate cardiac output, and an increased left ventricular filling pressure [ 2 , 3 ]. The DCM pathophysiology has been well-studied, and several mechanisms have been demonstrated to clarify how diabetes promotes cellular dysfunction [ 1 , 4 ]. Specifically, the high glucose levels enhance the production of advanced glycation end products (AGEs), leading to cardiovascular injury via crosslinking of extracellular matrix molecules [ 5 ].…”
Section: Introductionmentioning
confidence: 99%